+0  
 
+2
95
2
avatar+233 

solve this literal equation

nx+my=a

-nx+my=b

ManuelBautista2019  Oct 4, 2017
Sort: 

2+0 Answers

 #1
avatar+1483 
0

What does it call to be solved for?

HighSchoolCalculus  Oct 4, 2017
 #2
avatar+79881 
+1

I am solving for x and y

 

nx+my = a

-nx+my = b        add the two equations  and we get

 

2my  =  a + b        divide both sides by 2m

 

y  =  (a + b) / (2m)

 

Put this back into the first equation for y

 

nx  +  m [ (a + b) / (2m)]  = a      simplify

 

nx +  (a + b) / 2    = a           subtract (a + b) / 2   from both sides

 

nx  =  a  -  (a + b) / 2         we can write this as

 

nx  =   [ 2a  - a - b ]  / 2

 

nx =  [ a - b] / 2       divide both sides by n

 

x =  ( a - b ) / (2n)

 

 

cool cool cool

CPhill  Oct 4, 2017

6 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details